2021
DOI: 10.1103/physrevmaterials.5.014407
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption and x-ray magnetic circular dichroism in bulk and thin films of ferrimagnetic GdTiO3

Abstract: Perovskite rare-earth titanates are prototypical Mott insulators in which Ti 3+ ions with 3d 1 electronic configuration exhibit ferromagnetic or antiferromagnetic spin order, depending on the rare-earth size. This peculiar magnetic behavior has, however, been barely studied with element-specific probes, either in bulk or in thin films. The recent finding of fingerprints of ferromagnetism in two-dimensional electron gases at oxide interfaces involving rare-earth titanates has produced a surge of the interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(91 reference statements)
1
1
0
Order By: Relevance
“…A comparison with reference Ti 4+ spectra obtained for a SrTiO 3 single crystal clearly indicates that the additional XAS intensity in samples T3 and T4 appears in the energy range associated with the Ti 4+ spectral peaks, indicative of an overoxidation in samples T3 and T4. Such a partial conversion of Ti 3+ to Ti 4+ has been reported in several other XAS works on the RTiO 3 class of materials 19,20,25 . In order to confirm the effect of such oxidation on the magnetic properties, we performed XMCD measurements at 6 K, deep in the ferromagnetic phase.…”
Section: A Characterization Of Ytio3 Single Crystalssupporting
confidence: 81%
See 1 more Smart Citation
“…A comparison with reference Ti 4+ spectra obtained for a SrTiO 3 single crystal clearly indicates that the additional XAS intensity in samples T3 and T4 appears in the energy range associated with the Ti 4+ spectral peaks, indicative of an overoxidation in samples T3 and T4. Such a partial conversion of Ti 3+ to Ti 4+ has been reported in several other XAS works on the RTiO 3 class of materials 19,20,25 . In order to confirm the effect of such oxidation on the magnetic properties, we performed XMCD measurements at 6 K, deep in the ferromagnetic phase.…”
Section: A Characterization Of Ytio3 Single Crystalssupporting
confidence: 81%
“…Whereas this overoxidation effect can result from both cation vacancies and oxygen interstitials, the latter has been shown to be energetically favored 14 . The overoxidation effect has been the subject of recent studies, particularly of films, and has been shown to significantly affect magnetic and electronic properties 19,20 .…”
Section: Introductionmentioning
confidence: 99%